(Un)learning the city through crisis: lessons from Cape Town. (4th March 2019) - Robin, Enora; Chazal, Clémentine; Acuto, Michele; Carrero, Rocio
ABSTRACT: Scholarly research has shown the importance of moments of crisis, in particular the direct aftermath of urban crises, as opportunities to learn about urban vulnerabilities. However, if it is widely assumed that learning is important, in particular for resilience-building, we still know very little about how such learning occurs in a moment of crisis. This paper starts addressing this gap, arguing that moments of crisis constitute a specific type of 'learning space'. This proposition is taken forward through the analysis of a large-scale (social and humanitarian) urban crisis in the city of Cape Town. The paper maps out the emergence of multi-stakeholder knowledge networks throughout the crisis management process and explores the extent to which these were embedded into city-wide learning infrastructures after the crisis. It shows that moments of crisis represent an opportunity for ephemeral transsectorial knowledge coalitions to come about around issues that are made visible through the crisis itself. This can also be seen as an opportunity for potential learning spaces to open up.